2015
DOI: 10.1038/ncomms7029
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence for the co-evolution of hominin tool-making teaching and language

Abstract: Hominin reliance on Oldowan stone tools – which appear from 2.5mya and are believed to have been socially transmitted – has been hypothesised to have led to the evolution of teaching and language. Here we present an experiment investigating the efficacy of transmission of Oldowan tool-making skills along chains of adult human participants (N=184) using 5 different transmission mechanisms. Across six measures, transmission improves with teaching, and particularly with language, but not with imitation or emulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
414
2
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 446 publications
(431 citation statements)
references
References 55 publications
10
414
2
5
Order By: Relevance
“…This study of cultural change has advanced rapidly in recent years, part of a more general scientific focus on cultural evolution (Boyd & Richerson, 1996;Fitch, 2011c;Laland et al, 2010;Mesoudi et al, 2004). This research has recently taken a strong empirical turn both in humans (Kirby et al, 2008;Morgan et al, 2015;Smith & Kirby, 2008) and animals (Fehér, 2016;Fehér, Wang, Saar, Mitra, & Tchernichovski, 2009;Whiten et al, 1999). Because the term Blanguage evolution^can be interpreted either in terms of biological evolution of the language faculty or the cultural evolution of specific languages, Jim Hurford introduced the useful term Bglossogeny^to denote the latter specifically (Hurford, 1990).…”
Section: Cultural Aspects Of Language Evolutionmentioning
confidence: 99%
“…This study of cultural change has advanced rapidly in recent years, part of a more general scientific focus on cultural evolution (Boyd & Richerson, 1996;Fitch, 2011c;Laland et al, 2010;Mesoudi et al, 2004). This research has recently taken a strong empirical turn both in humans (Kirby et al, 2008;Morgan et al, 2015;Smith & Kirby, 2008) and animals (Fehér, 2016;Fehér, Wang, Saar, Mitra, & Tchernichovski, 2009;Whiten et al, 1999). Because the term Blanguage evolution^can be interpreted either in terms of biological evolution of the language faculty or the cultural evolution of specific languages, Jim Hurford introduced the useful term Bglossogeny^to denote the latter specifically (Hurford, 1990).…”
Section: Cultural Aspects Of Language Evolutionmentioning
confidence: 99%
“…In archaeological studies on social learning, the distinction between copying and proper teaching is rarely done (see, e.g., Morgan et al 2015). For example, MacDonald (2007, 398) concluded that 'descriptions of how children learn to use and manufacture hunting weapons indicate that teaching is unimportant relative to observation and practice'.…”
Section: Teaching and Cognitive Evolutionmentioning
confidence: 99%
“…Others have focused on related areas like learning and environmental adaptation (Shennan & Steel 1999), human ecology, information storage and cultural learning (Bentley & O´Brien 2013;Henrich 2004), evolution of modern thinking and increased working memory (Coolidge & Wynn 2009), the emergence of the social brain (Dunbar 1998;Gowlett et al 2012), co-evolution of hominin tool-making teaching and language (Morgan et al 2015), human evolution in the light of extant non-human tool users (Whiten et al 2009), neuroarchaeology and cognition (Stout et al 2015;Stout & Khreisheh, this issue), the successive development of a uniquely long period of human childhood, allowing imaginary play to expand (Nielsen 2011;Nowell 2010; this issue), stone tools and the evolution of human cognition (Nowell & Davidson 2010), to mention a few of many areas (for overview, see e.g. Beaune et al 2009;Renfrew et al 2009).…”
Section: Identified Cultural Learning As What Makesmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of such tests are not necessarily meant to be directly compared to archaeological data but instead to serve as a means of formally assessing and understanding the bounds of what is practically achievable when making or using stone tools in order to support or falsify potential motivating factors underlying patterns of tool production, use, morphology, and variability (Diez-Martin and Eren 2012; Lycett and Eren 2013b). There are several broad avenues of inquiry that have been investigated by means of experimental tests, including comparative morphology (Driscoll 2011;Eren and Lycett 2012;Gurtov, Buchanan, and Eren 2015;Presnyakova et al 2015;Williams and Andrefsky 2011); process controls (Patten 2002(Patten , 2005(Patten , 2009); tool use-life (Shott 2002); cognition and language (Geribas, Mosquera, and Vergès 2010;Mahaney 2014;Morgan et al 2015b;Putt, Woods, and Franciscus 2014;Stout et al 2000;Uomini and Meyer 2013); biomechanics (Faisal et al 2010;Key and Lycett 2011;Key and Dunmore 2015;Nonaka, Bril, and Rein 2010;Rolian, Lieberman, and Zermeno 2011;Richmond 2012, 2014); and the influence of stone raw material differences on lithic form (Archer and Braun 2010;Eren et al 2014b), production technology (Bar-Yosef et al 2012), tool function Galán and Domínguez-Rodrigo 2014;Rodríguez-Rellán, Valcarce, and Esnaola 2013;Waguespack et al 2009;Wilkins, Schoville, and Brown 2014), knapper skill (Duke and Pargeter 2015;Sampson 2011b, Eren et al 2011c;Stout and Semaw 2006;Winton 2005), use-wear accru...…”
Section: Replication As Testmentioning
confidence: 99%